Application of the mast® resistotyping scheme to arcobacterbutzleri strains isolated from commercial broilers - Halil İbrahim Atabay; Fuat Aydın (Eurasian Journal of Veterinary Sciences)
In this study, the applicability ol Mast Resistotyping scheme, which was originally developed lor the sub-typing of Campylobacter species, to Arcobacter butzleri strains isolated from broiler chickens was tested. The resistotyping scheme includes six antimicrobial agents comprising tetracycline (18µg); nalidixic acid (30µg); metronidazole (5µg); 2,3,5, triphenyltetrazolium chloride (1000µg); 5-fluorouracil (80µg) and sodium arsenite (30µg), which are impregnated to paper discs, and the theory of the system is based on determination of the resistance of the bacterial strains to those antibiotics. All strains tested were found sensitive to tetracycline and 2.3,5, triphenyltetrazolium chloride. Sixty-five percent, 15 %, 12 % and 9 % of the A. butzleri strains tested gave 66, 26, 06 and 46 code numbers, respectively, and 4 different resislotypes were obtained. Mast Campylobacter Resistotyping scheme was not found very suitable for the sub-typing of A. butzleri strains in this form, since there were few sub-types obtained with this system and the most strains gave the same code numbers (e.g. 22 of the 34 strains gave 66 code numbers). In addition, it is suggested that resistotyping scheme has to be made suitable for the sub-typing of Arcobacter species either by modifying the antimicrobial agents incorporated or by re-adjusting their concentrations.